Why Do Firms Train? Empirical Evidence on the First Labour Market Outcomes of Graduated Apprentices - Rob Euwals; Rainer Winkelmann (Institute for the Study of Labor (IZA), 2001)
The apprenticeship system is the most important source of formal post-secondary training in Germany. Our paper contributes to the ongoing debate as to why firms are willing to invest in such training even though many apprentices will leave the training firm soon after completion of the apprenticeship. Using German register data – the IAB Employment Sample – we find that apprentices staying with their training firm after graduation have (1) higher wages and (2) longer first-job durations than apprentices leaving the training firm. These results support theories according to which firms use the apprenticeship system to select and retain the more able apprentices, thereby recouping the costs of investing in skills that are portable in principle.
Keywords: C24; C41; J31; J44; J24; 330; Training; wages; job-duration; Betriebliche Weiterbildung; Bildungsertrag; Betriebszugehörigkeit; Duale Berufsausbildung; Deutschland